The Effect of WFH on Employee Performance and Work Stress Mediated by Work Motivation (Advertising Industry or Mass Media) - Ikhram, M. Abdi Dzil; Fuadip, Iqbal Ramadhani (Journal of International Conference Proceedings, 2023)
The Covid-19 pandemic is one of the problems that various fields of business must face. This study examines how the impact of work from home on employee performance and work stress is mediated by work motivation. This is due to changes in habits and internal conflicts related to performance experienced due to work stress. This change in habits has an impact on work stress and performance experienced by employees. This type of research is explanatory research which aims to test the research hypothesis. The research method uses a quantitative approach by distributing questionnaires as primary data and research respondents to all employees engaged in advertising or mass media. The analysis tool uses path analysis with SmartPLS software. The results of the study show that Work From Home affects employee performance and stress and is mediated by work motivation in the field of mass media